Phylogenomics Identifies an Ancestral Burst of Gene Duplications Predating the Diversification of Aphidomorpha. (8th November 2019) - Julca, Irene; Marcet-Houben, Marina; Cruz, Fernando; Vargas-Chavez, Carlos; Johnston, John Spencer; Gómez-Garrido, Jèssica; Frias, Leonor; Corvelo, André; Loska, Damian; Cámara, Francisco; Gut, Marta; Alioto, Tyler; et al.
Abstract: Aphids (Aphidoidea) are a diverse group of hemipteran insects that feed on plant phloem sap. A common finding in studies of aphid genomes is the presence of a large number of duplicated genes. However, when these duplications occurred remains unclear, partly due to the high relatedness of sequenced species. To better understand the origin of aphid duplications we sequenced and assembled the genome of Cinara cedri, an early branching lineage (Lachninae) of the Aphididae family. We performed a phylogenomic comparison of this genome with 20 other sequenced genomes, including the available genomes of five other aphids, along with the transcriptomes of two species belonging to Adelgidae (a closely related clade to the aphids) and Coccoidea. We found that gene duplication has been pervasive throughout the evolution of aphids, including many parallel waves of recent, species-specific duplications. Most notably, we identified a consistent set of very ancestral duplications, originating from a large-scale gene duplication predating the diversification of Aphidomorpha (comprising aphids, phylloxerids, and adelgids). Genes duplicated in this ancestral wave are enriched in functions related to traits shared by Aphidomorpha, such as association with endosymbionts, and adaptation to plant defenses and phloem-sap-based diet. The ancestral nature of this duplication wave (106–227 Ma) and the lack of sufficiently conserved synteny make it difficult to conclude whether it originated from a whole-genome duplication event or, alternatively, from a burst of large-scale segmental duplications. Genome sequencing of other aphid species belonging to different Aphidomorpha and related lineages may clarify these findings.